Indian agricultural trade in WTO regime - KAVITA, KAVITA; KUMAR, AJAY; SINGH, PARMINDER; SUMIT, SUMIT; MEHTA, V P (The Indian Journal of Agricultural Sciences, 2021)
Agriculture sector is the fundamental constituent of the Indian economy and this sector provides employment to more than (50%) population and contributes (17.32%) of gross domestic product. India is a net exporter of agricultural commodities with net exports earnings of US$ 28.66 billion in the year 2015. Nonetheless, liberalization, globalization, world Trade organization can greatly enhance the role of agriculture as an engine of growth in low-income countries like India by making it possible for the agricultural sector to grow considerably faster than the domestic consumption. It also increases the potential for enhance agricultural export from India to World. The present study was based on secondary data collected from the various published sources, viz. various issues of hand book of RBI, FAO Trade year Book, Statistical Abstract in India, indiastat.com, FAOSTAT etc. This study was carried out during 2018 at department of Agricultural Economics, CCSHAU, Hisar. The data were grouped into two periods (Pre-WTO and Post-WTO) depending upon the formation of world trade organization and its effect on export and import of agricultural sector, Period-I related to agricultural trade before formation of world trade organization and ranged from 1975-1994 and Period-II ranged from 1995-2015 which is the Post-WTO period. The data was analysed by using major analytical techniques like least square technique, tabular analysis, per centage share, growth rates and Coefficient of Variation. In this context, the present study analyses the trends, growth and instability in agricultural trade of India before and after WTO.